KINSHIP VOCATIVES IN ARABIC AS A REGISTER FEATURE OF SPOKEN DISCOURSE (A CASE STUDY FROM THE SYRIAN SERIES AL-KANDŪŠ الكندوش ) (BULLETIN OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. ORIENTAL LANGUAGES AND LITERATURES, 2025)
Background. This article presents a socio-semantic analysis of vocatives containing a kinship component as a register feature of the language code in the context of the oral dialectal speech of characters in the Syrian television series al-Kandūš. The action of the series takes place in Damascus in the first half of the twentieth century, which makes it possible to consider the characters' speech as representative of the urban Damascene sociolect, a variety of the Syrian dialect. The object of the study comprises 86 vocatives extracted from 35 episodes of the first season of the series (2021). The article describes the register characteristics of the most representative communicative situations in which vocatives with kinship terms occur. The aim is to identify and describe the register characteristics of vocatives with a kinship component as part of the language code in the context of their use.Methods. The theoretical framework is based on the principles of Systemic Functional Linguistics (M. A. K. Halliday, R. Hasan, J. Martin, P. White), particularl y the theory of register (Halliday, 1985; Hasan, 1999; Martin, & White, 2005) as an analytical tool for describing the relationship between linguistic form and social context. A socio-semantic approach was applied to analyse linguistic units in their real communicative use, with each vocative examined in context (in use). Vocatives with a kinship component were identified as one of the register characteristics of mode (language code), determined by the social relationships between participants (tenor) and the thematic domain (field). The main research method was socio-semantic analysis (Kress, & van Leeuwen, 2006). The study also employed the descriptive method, pragmatic analysis of speech acts (following J. Searle), and functional-syntactic analysis (to establish the relationship between the vocative's position in the sentence and its function).Results. It was found that vocatives with a kinship component as the language code (mode) in oral interaction are determined by the following extralinguistic register characteristics: the configuration of the speakers' social roles (tenor) and the thematic domain (field). The choice of vocative depends on the status hierarchy, age, gender, degree of familiarity, and emotional closeness between interlocutors. The thematic domain includes domestic and family communication, situations of social support, conflict interaction, and public discourse. The language code is represented by the Damascene sociolect, in which vocatives with a kinship component function as markers for identifying the addressee, expressing emotional closeness, or, conversely, as means of increasing social distance and structuring dialogue.СonclusіIons. The analysis showed that the form, syntactic position, and pragmatic function of vocatives as part of the language code in situations of informal oral communication in the Syrian dialect depend on three register parameters: the thematic domain of interaction, the social roles and status of the speakers. The data also record and describe cases of social role inversion realised through vocatives with a kinship component. In informal discourse, such vocatives perform an expressive function, while in conflict speech acts they serve as a means of increasing social distance.Prospects for further research include expanding the sample to other Arabic dialects, analysing etiquette formulas across different registers, and conducting a comparative study of vocatives in various situational contexts of oral interaction.
Keywords: Syrian dialect; spoken discourse; vocatives